2003
DOI: 10.1063/1.1592295
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the capacitance–voltage characteristics measured by the scanning capacitance microscope

Abstract: A scanning capacitance microscope (SCM) can measure the local capacitance–voltage (C–V) characteristics of a metal-oxide-semiconductor structure formed by the SCM probe tip and a doped semiconductor sample. A common realization of the SCM depends on a parallel atomic force microscope, which includes a laser focused on the end of the cantilever to monitor the position of the probe tip. In this configuration, it is found that the stray light from the laser can dramatically affect the measured C–V curve. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Indeed, when the laser was turned off using the "dark lift" mode, we did not observe any measureable affect on the SCM images, which is different from the literature 10,11 and is likely a result of a different sample setup. Intentionally connecting the contacts of a live device so that every local area of the front and back contacts are shorted could result in a different sample condition from an unintentionally, and unevenly, shorted device.…”
Section: Methodscontrasting
confidence: 49%
“…Indeed, when the laser was turned off using the "dark lift" mode, we did not observe any measureable affect on the SCM images, which is different from the literature 10,11 and is likely a result of a different sample setup. Intentionally connecting the contacts of a live device so that every local area of the front and back contacts are shorted could result in a different sample condition from an unintentionally, and unevenly, shorted device.…”
Section: Methodscontrasting
confidence: 49%
“…7) To overcome these drawbacks, we have applied an all-metal probe under frequency modulation (FM) control that requires no optical detection technique. Figure 1 is a schematic of the FM-SCM setup.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 The SCS investigations by Buh et al indicated that both the AFM laser beam and the modulation voltage (MV) may distort SCS profiles of a metal-oxide-semiconductor (MOS) capacitor. 18 Moreover, the humidity-induced hysteretic behavior of SCS was studied, exploring the importance of environmental control for SCM measurements. 19 Since SCM is equipped with a lock-in amplifier to measure the dC/dV signals, it is necessary to apply a MV during SCM measurements.…”
mentioning
confidence: 99%